Academic hardiness and academic self-efficacy in graduate studies. Issue 5 (29th July 2019) - Cheng, Ying-Hsueh; Tsai, Chin-Chung; Liang, Jyh-Chong
ABSTRACT: The purpose of the study was to measure graduate students' academic hardiness (GSAH) and academic self-efficacy (GSASE) and to examine the relationships between the two. A total of 202 graduate students across disciplines were recruited to complete two questionnaires (GSAH and GSASE). Results of exploratory factor analyses showed that the GSAH and GSASE were reliable for assessing graduate students' academic hardiness and academic self-efficacy. Comparing master's and doctoral students' scores in the GSAH and GSASE scales, we found that doctoral students outperformed master's students. The findings also revealed that three dimensions of GSAH (commitment, control of affect, and challenge) were strong predictors of graduate students' academic self-efficacy. These results confirm and strengthen the relation between graduate students' academic hardiness and academic self-efficacy. This study calls attention to graduate students' ability to recognize and appraise causes of their failure and to learn how to overcome academic difficulties.